Borehole seismic monitoring of a small-scale CO2 injection - The CO2CRC Otway project feasibility study - Pevzner, Roman; Urosevic, Milovan; Gurevich, Boris (2015)
The CO2CRC Otway project is the first Australian demonstration of safe geological storage of carbon dioxide. The first stage of the project, concluded in 2010, was focussed on injection of more than 66,000 tonnes of CO2/CH4 gas mixture (~80% of CO2) into a depleted gas reservoir located at approximately 2 km depth through a purposely drilled CRC-1 well. The next stage of the project, which is currently underway examines small scale (up to 15,000 tonnes) gas injection into a saline aquifer located at 1.5 km depth using CRC-2 well. In this paper we use full elastic 3D finite difference modelling to evaluate the level of time-lapse signal on walk-away VSP data acquired in CRC-1 and CRC-2 wells. The results are used to optimise borehole seismic acquisition parameters.